Which graft should be used for the pediatric transcanal endoscopic type 1 tympanoplasty? A comparative clinical study. (June 2019) - Sen, Alper; Özdamar, Kadir
Abstract: Objectives: To compare the functional and anatomical success rates of the fascial versus perichondrial grafts in pediatric endoscopic type 1 tympanoplasties. Methods: This retrospective clinical study was conducted on 40 pediatric patients (23 females and 17 males; mean age: 10.0 ± 1.7 years; the age range: 6–13) who were operated with a transcanal endoscopic type 1 tympanoplasty. The study participants were assigned to two groups by graft types. The patients were assigned to either the tragal cartilage perichondrium group (Group A) or the fascia of the temporal muscle (Group B). The groups were compared according to the pre- and postoperative air-bone gaps and to the status of the tympanic membrane. Results: There were not any statistically significant differences between the groups in terms of the distribution of age, gender, the operation sites, the duration of the operation, MERI scores or the size of the perforation (all p values > 0.05). The graft retention success rates were 94.7% and 90.5% in Group A and Group B, respectively. There were no statistically significant differences between the two groups in terms of the graft retention success rates (p = 0.609). The functional (audiological) success rate was statistically higher in Group B compared to Group A (p = 0.044). Conclusion: Perichondrium and fascia grafts were found out to be acceptable for use in pediatric endoscopic tympanoplasties. The functional success rates were higher in the fascia group. We also recommended the fascia as a graft in pediatric transcanal endoscopic type 1 tympanoplasties.